Extensão da responsabilidade civil do agente de turismo frente ao consumidor na Legislação Brasileira - Siqueira, Milton Lamenha de (Revista Turismo em Análise, 1995)
This article brings a classification and activities of Travel Agencies in Brazil. It analyses the civil responsibility in Brazilian Law. With grounds on the Civil Code, Consumers Defense Code. Tourism Law and Aeronautics Law. It ends stressing that Tourism Agents, in their relations with consumers, should fulfillthe requirements of the Law referred to them and at the same time, the Consumers Defense Code in those aspects in which they do not conflict.